Groundwater extraction-induced land subsidence: a geodetic strain rate study in Kelantan, Malaysia. Issue 2 (4th May 2019) - Yong, Chien Zheng; Denys, Paul H.; Pearson, Christopher F.
Abstract: Kelantan is one of the highest groundwater-consumption states in Malaysia. The groundwater extraction provides an alternative solution for accessing a fresh water supply. However, over-exploitation of groundwater can lead to harmful geomorphological effects. We investigate the deformation rate due to land subsidence in Kelantan, Malaysia, using 17 years of GPS time-series (1999.0 – 2016.0) recorded at 11 GPS sites. Our results agree with a previous study, suggesting that northern Kelantan is subsiding at a maximum rate of 4.22 ± 0.17 mm/yr (1σ confidence level). The region also shows higher ground deformation rates than the other parts of Peninsular Malaysia (0.22 ppm/yr). In addition to the observed vertical subsidence, there is a corresponding horizontal deformation signal that manifests as strain accumulation. The dilatation strain rate shows a clear contractional pattern along the SW-NE trend of the Kelantan River, which is associated with the extensional signal in the surrounding regions.